Diva vocaloids a new sensation in the music industry - Martinez, Muviel Justine Coronado; Manalili, Perlita G.; University of the Philippines. College of Mass Communication (2013)
"This thesis investigates the effects of Vocaloid to the Filipino audience. Vocaloid is a voice synthesizer software which is used to create music without the presence of human singers. As a mean of expansion and improvement in advertising, it has been accompanied with anime-like mascots to cater to the consumers' visual stimuli. This phenomenon has created a wide range of fans that express their following for Vocaloid in various ways: music consumption, music production and cosplay. As an exploration to this new element in the music and animation industries, this thesis utilizes concepts of Uses and Gratification and Identification to better understand the rationale for Vocaloid's increasing following as well as the effects that it create among its subscribers. Using semi-structured interviews, the researcher was able to collect first-hand data from Vocaloid fans as to why and how much they are inclined to Vocaloid. The variety of characters, the new take on musical genres and the freedom for consumers to be their own producers as well -these are the reasons why Vocaloid fans subscribe to the software and its products. The findings lead to the conclusion that Filipino Vocaloid fans prioritize the newness, diversity and room for creativity that Vocaloid offers. It proves that the Filipino Vocaloid fans are active consumers: they are aware of the motivations behind their media choices and they belong to the community that participate in the new forms of interactivity in media."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Singing voice synthesizers; Mass media and music -- Philippines; Production music